Univariate Integration via Space Extension Based No Fluctuation Approximation - Üsküplü, Sevda; Demiralp, Metin (AIP Publishing, 2008)
The fluctuationlessness approximation gives powerful and easily utilizable solutions for a lot of applications of numerical analysis. For example, it helps us to create univariate numerical integration schemes which converge very rapidly. On the other hand, the space extension approaches aim to convert equations into some other structures which can be handled more easily. It is possible to apply this approach to the solutions obtained with fluctuationlessness approximation in order to improve the quality of approximation.